SYNTHESIS OF 5, 7-DIHYDROXY-6, 8-DI-C-PRENYL-4?-O-PRENYL-FLAVANONE (Biological Sciences - PJSIR, 2004)
The prenylated flavanone (9) has been synthesized from phloroacetophenone (1). All the new products have been characterized by the spectral data and microanalysis.